Incidencia de la motricidad en el desarrollo físico e intelectual de los niños y niñas de primer año de las escuelas de educación básica 23 de Abril y Guadalupe Fernández de Castro de la parroquia la Iberia periodo lectivo 2012 - 2013. - Guamán Saritama, Diana Leticia (2014)
Early education and preschool, aims to develop children in their physical and intellectual capacities, being the object of study motor development, as development axis to acquire the skills and abilities according to their capabilities. This research was developed in basic education schools April 23 and Guadalupe Fernandez de Castro Iberia Parish belongs to Canton Machala, for which, the following hypothesis is proposed: The incidence of motor development physical and intellectual development of children in the first year of elementary schools April 23 and Guadalupe Fernandez de Castro is limited due to the implementation of routine activities that fail to foster the creativity of children. To verify its validity was performed: a literature review, survey teachers and chips watching children, instruments that were used to develop the statistical tables and charts. As a result follows the following general conclusion: The incidence of motor skills in physical and intellectual development of children first year of basic education schools April 23 and Guadalupe Fernandez de Castro is satisfactorily low, Lacking the necessary and sufficient resources for this activity. In deriving the hypothetical approaches as affirmative, it has set the development of a methodological guide to promote physical intellectual development of children in the first year of treatment schools.